2004
DOI: 10.1111/j.1365-246x.2004.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Sea-surface observations of the magnetic signals of ocean swells

Abstract: S U M M A R YOcean swells have a magnetic signal, caused by the motional induction of sea water moving in the steady main magnetic field of Earth. To check the character of such signals at the sea surface, a magnetometer has been set free from a ship to float unrestricted on the surface of the ocean for periods of several days. The path of the floating magnetometer was tracked by satellite; this procedure enabled also the eventual recovery of the magnetometer by the ship.Superimposed upon a background of slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…( 9) Sea-surface measurements as reported in Lilley et al (2004) combined with forecast knowledge of the ocean swell at the time confirm that to within the errors involved, actual observed signals are consistent with this theory. An example of the signal from Lilley et al (2004) is shown in Figure 2.…”
Section: Motional Inductionsupporting
confidence: 70%
See 3 more Smart Citations
“…( 9) Sea-surface measurements as reported in Lilley et al (2004) combined with forecast knowledge of the ocean swell at the time confirm that to within the errors involved, actual observed signals are consistent with this theory. An example of the signal from Lilley et al (2004) is shown in Figure 2.…”
Section: Motional Inductionsupporting
confidence: 70%
“…The point is made in Lilley et al (2004) that often the ocean swell signal will be a sharp spectral peak, for a stationary magnetometer. The present paper examines how a moving aircraft sees a different frequency, and how this frequency translates into an apparent spatial wavelength if it is preserved in data that are then plotted in map form.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wave heights and periods of ocean swells are usually several metres and around 13 s. These ocean swells can generate magnetic signals up to 5 nT [26]. Typical tide flow can induce a magnetic field of 20-30 nT.…”
Section: Introductionmentioning
confidence: 99%